STRATEGY FOR IMPROVING THE QUALITY OF LIVABILITY AS AN EFFORT TO REALIZE A SUSTAINABLE TANJUNGBALAI CITY - Rudiansyah Nasution; Cut Nuraini; Abdi Sugiarto (Bulletin of Engineering Science, Technology and Industry, 2025)
Improving the quality of livability in Tanjungbalai City is highly dependent on urban planning and management that integrates social, economic, and environmental aspects. This study aims to explore strategies that can be applied to improve the quality of livability through the principle of sustainability. The role of local governments in formulating policies and providing basic infrastructure that is environmentally friendly is crucial, while the community also has an important role in supporting policy implementation and protecting the environment. Synergy between the government and the community is key to realizing a sustainable and livable Tanjungbalai City. Strategies that can be applied include increasing community participation, developing sustainable infrastructure, increasing green open spaces, implementing environmentally friendly technologies, and environmental awareness education.